2007
DOI: 10.1016/j.molcata.2007.09.022
|View full text |Cite
|
Sign up to set email alerts
|

CO–ethene copolymerisation catalysed by [PdCl2(PPh3)2]/PPh3/HCl in MeOH

Abstract: The system [PdCl 2 (PPh 3 ) 2 ]/PPh 3 /HCl catalyses the carbonylation of ethene in MeOH as a solvent to give methyl propanoate (MP) or a polyketone (PK).The influence of temperature, Pd/P, CO/ethene and Pd/HCl ratios, and concentration of H 2 O on the catalytic activity has been studied. The catalytic system is active only in the presence of HCl and is stable when P/Pd is ≥6/1 up to 110• C. At 100• C, with Pd/P/HCl = 1/6/1600 (HCl initially added), under 6.0 MPa total pressure, the main product is MP at 1.0 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…150 as (moles of ethene absorbed)(mol·Pd·h) −1 , whereas when ethene:CO = 40:20, the main product is a PK of moderate M n (2000–2500 g·mol −1 , TOF = 300 h −1 ), the formation of MP being almost suppressed. It was suggested that the acid, in addition to stabilizing the Pd-H initiator, could also destabilize the β- and γ-chelates through protonation of the oxygen atoms coordinating the metal centre, thus easing the chain growing process [68].…”
Section: Influence Of the Ligand On The Product Formationmentioning
confidence: 99%
“…150 as (moles of ethene absorbed)(mol·Pd·h) −1 , whereas when ethene:CO = 40:20, the main product is a PK of moderate M n (2000–2500 g·mol −1 , TOF = 300 h −1 ), the formation of MP being almost suppressed. It was suggested that the acid, in addition to stabilizing the Pd-H initiator, could also destabilize the β- and γ-chelates through protonation of the oxygen atoms coordinating the metal centre, thus easing the chain growing process [68].…”
Section: Influence Of the Ligand On The Product Formationmentioning
confidence: 99%
“…Tooze et al modified the process to produce methyl propanoate, which is the most straightforward "polymer" obtained after quenching with methanol, i.e., the process operates for one cycle only (Figure 3). Since the initial development work on ethene-CO polymerisation by Drent, the mechanism of this process has been well studied [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Tooze et al modified the process to produce methyl propanoate, which is the most straightforward "polymer" obtained after quenching with methanol, i.e., the process operates for one cycle only (Figure 3).…”
Section: Introductionmentioning
confidence: 99%